Protection of database under actionable torts - Nazura Abdul Manap, (Fakulti Undang - Undang, 2008)
The need for legal protection for database is derived mainly from the universal problem of piracy. Database piracy has for years become a threat to database producers, primarily because of its nature of “easily susceptible for copying”. Advances in digital technology have facilitated the creation of databases. The technology makes possible for a large amount of data to be created and converted to a digital form. The same technology used in increasing the value of database, may also permit quick and easy reproduction of those databases or substantial portion of the data contained in it. This encourages the act of “free riding”. In the event that copyright, contract and self-help technical devices fail to repress wholesale copying, the law of actionable torts would suffice to prohibit the free riding activities of database, including parasitical or market-destroying business practices. In Malaysia, the courts should be willing to apply tortious principles in appropriate database cases. This would be a viable alternative to heavy-handed intellectual property legislation